61 2018 Southern Section Extension Forum: Collaborating to meet the needs of clientele. (29th July 2019) - Stewart, Lawton; Mullenix, Mary K; Hersom, Matt; Smith, Jason; Moriel, Philipe; Rhinehart, Justin D
Abstract: A two-day forum was held at the University of Tennessee (UT) Middle Tennessee Research and Education Center to foster collaborative efforts between Extension specialists and county or area agents across the southern United States. The forum was attended by 28 specialists and 18 county or regional agents from across the Southern Section of ASAS. The forum began with a tour of the UT Heifer Development Center. The forum was split into three sessions and included: 1. Transfer of knowledge (Demonstration research), 2. Developing formal education for Extension agents, and 3. Collaborating across state lines to develop Extension Programs. Within each section, a brief presentation was given, followed by break-out sessions to discuss success stories from each state and potential programs to implement. From the break-out session, areas of need identified primarily focused on the development of support resources for Extension agents. Needed outputs identified included a resource guide for conducting on-farm research and demonstration projects with county and regional Extension agents, defining a regional process to provide formal distance education for agents, and development of online coursework and training tools for agents for continuing education. Assessment data indicate that participants had completed an average of 8.4 (± 6.65, range 0.5 to 24) years of service. Agents were asked to rank their level of confidence, using a 5-point Likert scale, with three tasks. Averages (SEM) of that self-assessment are indicated in Table 1. The 2018 Southern Section Extension Forum was a successful effort to bring together collaborators to identify needs and propose programs to improve the impact of Extension.